Lời giải:
Trừ 2 PT theo vế ta có:
$x^2y-xy^2=y^2-x^2$
$\Leftrightarrow x^2y-xy^2+x^2-y^2=0$
$\Leftrightarrow xy(x-y)+(x-y)(x+y)=0$
$\Leftrightarrow (x-y)(xy+x+y)=0$
$\Rightarrow x-y=0$ hoặc $xy+x+y=0$
Nếu $x-y=0\Leftrightarrow x=y$. Thay vào PT(1):
$x^3+2=x^2$
$\Leftrightarrow (x+1)(x^2-2x+2)=0$
$\Leftrightarrow (x+1)[(x-1)^2+1]=0$
Hiển nhiên $(x-1)^2+1>0$ nên $x+1=0$
$\Leftrightarrow x=-1$. Vậy $(x,y)=(-1,-1)$
Nếu $xy+x+y=0$
$\Leftrightarrow xy=-(x+y)$. Thay vào pt(1):
$x(-x-y)+2=y^2$
$\Leftrightarrow 2=x^2+xy+y^2=(x+y)^2-xy=(x+y)^2+(x+y)$
$\Leftrightarrow (x+y)^2+(x+y)-2=0$
$\Leftrightarrow (x+y-1)(x+y+2)=0$
$\Rightarrow x+y=1$ hoặc $x+y=-2$
Nếu $x+y=1$ thì $xy=-1$. Theo định lý Viet thì $x,y$ là nghiệm của $T^2-T-1=0$
$\Rightarrow (x,y)=(\frac{1+\sqrt{5}}{2}, \frac{1-\sqrt{5}}{2})$ và hoán vị
Nếu $x+y=-2$ thì $xy=2$. Theo định lý Viet thì $x,y$ là nghiệm của pt $T^2+2T+2=0$
Hiển nhiên pt này vô nghiệm nên loại
Vậy...........